Rethinking mental wellness among adolescents: an integrative review protocol of mental health components - Zaida Orth; Brian van Wyk (Systematic Reviews, 2022)
Abstract Background Adolescents have been overlooked in global public health initiatives as this period is generally considered to be the healthiest in an individual’s life course. However, the growth of the global adolescent population and their changing health profiles have called attention to the diverse health needs of adolescents. The increased attention toward adolescent health has accentuated existing gaps as global health reports have emphasised that there is a continued need for valid and reliable health data. In this context, evidence has shown that mental health issues constitute one of the greatest burdens of disease for adolescents. This integrative review aims to unpack the meaning of mental wellness among adolescents and its associated constructs by analysing and synthesising empirical and theoretical research on adolescent mental wellness. In doing this, we will develop a working definition of adolescent mental wellness that can be used to develop an instrument aimed at measuring adolescent mental wellness. Methods The integrative review is guided by the five steps described by Whittemore and Knafl. A comprehensive search strategy which will include carefully selected terms that correspond to the domains of interest (positive mental health/mental wellness) will be used to search for relevant literature on electronic databases, grey literature and government or non-governmental organisations (NGO) websites. Studies will be included if they describe and/or define general mental wellness in adolescent populations aged 10–19. The screening and reporting of the review will be conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data from the integrative review will be analysed using narrative framework synthesis for qualitative and quantitative studies. Discussion This integrative review aims to search for and synthesise current research regarding adolescent mental wellness to identify how wellness is being described and conceptualised. We aim to identify gaps and to contribute to a more comprehensive definition of mental wellness which can aid in the development of an age- and culturally appropriate measure of adolescent mental wellness.